Transforming Local Entrepreneurs into Digital Champions: A Strategic Framework for Sustainable and Resilient Ventures - Muhammad Awaluddin (Journal of Digital Business and Global Economy, 2026)
The rise of the digital economy has redefined competitiveness for MSMEs, positioning digital empowerment as a critical pathway for business resilience and long-term sustainability. This study aims to formulate a strategic framework that explains how local entrepreneurs can progress toward becoming digital champions through structured transformation stages. Adopting a descriptive qualitative approach, the research analyses interdisciplinary literature and documentary datasets, supported by empirical evidence from national MSME empowerment programs. Data were collected from policy briefs, government reports, academic studies, and case documentation, and examined using content interpretation, framework mapping, and theoretical empirical synthesis. Findings reveal that MSME transformation is driven by the interplay of mindset, capability development, and ecosystem collaboration, which are further operationalized through the CHAMP model Customer Value, Human-Centered Innovation, Alliance and Co-Creation, Market Expansion, and Purpose-Driven Growth. Four sequential transformation phases Go Modern, Go Digital, Go Online, and Go Global demonstrate clear pathways for business reinforcement, market expansion, and global competitiveness. The study concludes that scalable MSME empowerment requires integrated interventions that simultaneously strengthen entrepreneurial identity, digital skills, and ecosystem accessibility. Future initiatives are recommended to implement longitudinal evaluation and incorporate emerging technologies to maintain adaptability in increasingly dynamic markets.